Rescuing key native traits in cultured dermal papilla cells for human hair regeneration - Abreu, Carla M. (2021)
Introduction: The dermal papilla (DP) represents the major regulatory entity within the hair follicle (HF), inducing hair formation and growth through reciprocal interactions with epithelial cells. However, human DP cells rapidly lose their hair inductive ability when cultured in an epithelium-deficient environment. Objectives: To determine if the conditioned medium collected from interfollicular keratinocytes (KCs-CM) is capable of improving DP cell native properties and inductive phenotype. Methods:DP cells were cultured with KCs-CM both in 2D and 3D culture conditions (spheroids). Further, the hair-inductive capacity of DP cells precultured with KCs-CM was tested in a hair reconstitution assay, after co-grafting with human keratinocytes in nude mice. Results:We demonstrate that KCs-CM contributes to restore the inductivity of cultured human DP cells in a more effective mode than the conventional 3D-cultures. This is supported by the higher active alkaline phosphatase (ALP) levels in DP cells, the improved self-aggregative capacity and the reduced expression of α-SMA and the V1-isoform of versican. Moreover, DP cells cultured with KCs-CM displayed a secretome profile (VEGF, BMP2, TGF- β1, IL-6) that matches the one observed during anagen. KCs-CM also enhanced DP cell proliferation, while preventing cells to undergo morphological changes characteristic of high passage cells. In opposition, the amount of collagenous and non-collagenous proteins deposited by DP cells was lower in the presence of KCs-CM. The improvement in ALP activity was maintained in 3D spheroidal cultures, even after KCs-CM retrieval, being superior to the effect of the gold-standard culture conditions. Moreover, DP cells cultured with KCs-CM and grafted with human keratinocytes supported the formation of HF- and sebaceous gland-like structures in mice. Conclusion:The proposed strategy encourages future cell-based strategies for HF regeneration not only in the context of hair-associated disorders, but also in the management of wounds to aid in restoring critical skin regulatory appendages.